"No, no Maama! Say 'Shaatir ya Ouledee Shaatir'!" Children's agency in language use and socialisation. (June 2019) - Said, Fatma; Zhu, Hua
Aims and objectives: This paper investigates how children in multilingual and transnational families mobilise their multiple and developing linguistic repertoires creatively to assert their agency in language use and socialisation, and why these acts of agency are conducive to successful maintenance of the so-called "home", "community" or "minority" language. Methodology: Close, qualitative analysis of mealtime multiparty conversations is carried out to examine children's agency in language use and socialisation. Data and analysis: Twelve hours of mealtime conversations within one Arabic and English-speaking multilingual family in the UK were recorded over a period of eight months. The excerpts selected for analysis in this paper illustrate how agency is enacted in interaction. Findings: The data analyses of the family's language practices reveal both their flexible language policy and the importance the family attaches to Arabic. The children in this family are fully aware of the language preferences of their parents and are capable of manipulating that knowledge and asserting their agency through their linguistic choices to achieve their interactional goals. Originality: This paper explores how Arabic is maintained as a minority language by second and third generations of Arabic-speaking immigrants in the UK through close analysis of conversations. Significance: The findings contribute to the current discussions of family language policy and maintenance by demonstrating children's agentive and creative roles in language use and socialisation. Three factors are identified as the reason for the successful language learning, use and maintenance of Arabic: firstly, a family language policy that has a positive multilingual outlook; secondly, family relationship dynamics that connect and bond family members; and thirdly, the children's highly developed ability to understand their parents' language preferences.